Analisis Rugi-Rugi (Losses) Transformator Daya 150/20 KV di PT. PLN (Persero) Gardu Induk Sutami ULTG Tarahan - Hendri Elnizar; Herri Gusmedi; Osea Zebua (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2021)
In general, in the distribution of electrical energy, there will always be losses. In a transformer, there are two types of losses, namely technical losses and non-technical losses. Non-technical losses are caused by things outside of system performance, such as accidents, natural disasters, human negligence, and so on. Meanwhile, technical losses are caused by two things, namely copper losses and core losses. Technical losses in the transformer cause the efficiency of the electricity supply to be low. Therefore the author will make a thesis entitled